1994
DOI: 10.1152/ajpheart.1994.267.3.h887
|View full text |Cite
|
Sign up to set email alerts
|

Testosterone increases thromboxane A2 receptor density and responsiveness in rat aortas and platelets

Abstract: Testosterone has been implicated as a risk factor for cardiovascular diseases. Thromboxane (Tx) A2 is an important pathophysiological mediator for thrombotic vascular diseases. This study investigated the effects of testosterone on platelet and vascular TxA2 receptors. Male rats were treated with either testosterone cypionate for 2 wk, sham operated, castrated, or castrated and treated with testosterone cypionate for 2 wk. Treatment of intact rats with testosterone significantly (P < 0.001) increased the TxA2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
55
0
1

Year Published

2000
2000
2012
2012

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 0 publications
5
55
0
1
Order By: Relevance
“…However, concentration-response curves to the TP agonist U-46619 were identical in pressurized MCA segments from ORX and ORXϩT rats. This finding implies there was no change in cerebral artery TP receptors, in contrast with studies on other vascular beds, cultured vascular smooth muscle, and platelets in which testosterone increased TP receptor density and U-46619 responses (1,17,21,27,34). Because the mechanisms underlying testosterone effects on TP receptors are unknown, it is difficult at this point to explain why cerebral arteries differ.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…However, concentration-response curves to the TP agonist U-46619 were identical in pressurized MCA segments from ORX and ORXϩT rats. This finding implies there was no change in cerebral artery TP receptors, in contrast with studies on other vascular beds, cultured vascular smooth muscle, and platelets in which testosterone increased TP receptor density and U-46619 responses (1,17,21,27,34). Because the mechanisms underlying testosterone effects on TP receptors are unknown, it is difficult at this point to explain why cerebral arteries differ.…”
Section: Discussionmentioning
confidence: 66%
“…Testosterone was shown to increase the density of TxA 2 -endoperoxide receptors (TP) in platelets (1,27) and vascular smooth muscle cells cultured from the rat aorta or canine coronary artery (18,26). Testosterone also increased constrictor responses to the TxA 2 mimetic U-46619 in the isolated aorta and coronary and renal arteries (17,21,27,34).…”
mentioning
confidence: 99%
“…Studies have shown that testosterone increases the levels of vascular smooth muscle thromboxane A 2 receptors in the aorta (28). Moreover, testosterone treatment enhances the vasoconstrictor response of thromboxane A 2 in the coronary circulation (21,28).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, testosterone treatment enhances the vasoconstrictor response of thromboxane A 2 in the coronary circulation (21,28). Furthermore, it has been shown that testosterone treatment inhibits prostacyclin synthesis in rat aorta smooth cells in culture (36).…”
Section: Discussionmentioning
confidence: 99%
“…However, endothelial injury as a result of lipid profile alterations and establishment of atherosclerosis could explain the impairment in endothelium-dependent pathway through decreased NO production. Also, the increase in TxA2 receptor density in vessel walls as a result of AAS treatment results in impaired endothelial-independent vasodilator pathways [50]. Further studies should be carried out to reveal more information on cellular and molecular processes related to the role of AAS on vasoreactivity.…”
Section: Impaired Vasodilatationmentioning
confidence: 99%